Supporting Muslim students a guide to understanding the diverse issues of today's classrooms - Mahalingappa, Laura 1975-; Rodriguez, Terri 1967-; Polat, Nihat (Rowman & Littlefield, 2017)
This book is a practical guide for educators who are working with Muslim youth in PK-12 schools to understand issues that may impact Muslim students today. It outlines basic information about the Muslim community and presents topics such as peer relationships, bullying, and anti-bias pedagogy, through school-based vignettes and case studies.